2013
DOI: 10.1002/jbm.a.34742
|View full text |Cite
|
Sign up to set email alerts
|

A new TGF‐β3 controlled‐released chitosan scaffold for tissue engineering synovial sheath

Abstract: The post-operative outcome of flexor tendon healing remains limited by flexor tendon adhesion that reduces joint range of motion. Despite improvement in different methods, peritendinous adhesion formation continues to present a formidable challenge. Recent studies showed that transforming growth factor-β3 (TGF-β3) may be the key factor to reducing adhesion formation in skin or tendon. In this study, we designed a novel type of tissue engineering synovial sheath containing TGF-β3, to prevent flexor tendon adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Previous studies have established a role for TGF-β signaling in tendon healing by demonstrating that inhibition of neutralization of TGF-β1 and β2, or the addition of TGF-β3 can decrease adhesion formation (8,26,27). A novel TGF-β3 controlled-released chitosan scaffold has been developed for tissue engineering of the synovial sheath (28). The present study focused on the effect of TGF-β3, and the underlying the TGF-β/Smad signaling pathway on wound healing.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have established a role for TGF-β signaling in tendon healing by demonstrating that inhibition of neutralization of TGF-β1 and β2, or the addition of TGF-β3 can decrease adhesion formation (8,26,27). A novel TGF-β3 controlled-released chitosan scaffold has been developed for tissue engineering of the synovial sheath (28). The present study focused on the effect of TGF-β3, and the underlying the TGF-β/Smad signaling pathway on wound healing.…”
Section: Discussionmentioning
confidence: 98%
“…168 Hence, it is thought that the incorporation of this factor in scaffolds may be vital in reducing adhesion formation in healing tendons. 169 PDGF-BB and FGF were shown to significantly increase canine flexor tendon fibroblast proliferation and collagen production when tested in-vitro and in-vivo. 170 171 Transfer of an exogenous PDGF-B gene to rat tenocytes has also been shown to increase collagen I gene expression in-vitro, suggesting that PDGF gene transfer may offer a novel way of promoting flexor tendon healing.…”
Section: Growth Factorsmentioning
confidence: 94%
“…To induce tenogenic differentiation, encapsulated PDLSCs and GMSCs as well as hBMMSCs (2×10 6 cells in 1 mL of TGF-β3-loaded alginate microspheres) were cultured in a tenogenic medium containing DMEM with 15% FBS, 2 mM L-glutamine, 100 nM Dex, 100 3M ascorbic acid, 2 mM sodium pyruvate (R&D Systems Inc), 100 U/mL penicillin, and 100 μg/mL streptomycin [26]. Cell-free RGD-coupled alginate microspheres without TGF-β3 were used as the negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TGFβ signaling is a potent inducer of Scleraxis (Scx), a basic helix-loop-helix (bHLH) transcription factor gene that is a unique marker for the tendon cell fate in vitro and in vivo , demonstrating a vital role for the TGF-β signaling pathway in tendon repair and regeneration [2325]. Among the members of the TGF-β superfamily, TGF-β3 is of particular interest as it is an isoform that has been associated with promoting dermal wound and tendon healing without fibrotic scar formation [26,27]. Other studies have confirmed that differentiation of MSCs driven by TGF-β3 can promote tendon tissue formation and may provide a promising modality of treatment for tendon regeneration and repair [2427].…”
Section: Introductionmentioning
confidence: 99%